Modulatory Effects of Monoamines and Perineuronal Nets on Output of Cerebellar Purkinje Cells - Hirono, Moritoshi; Karube, Fuyuki; Yanagawa, Yuchio (Frontiers in Neural Circuits, 2021)
Classically, the cerebellum has been thought to play a significant role in motor coordination. However, a growing body of evidence for novel neural connections between the cerebellum and various brain regions indicates that the cerebellum also contributes to other brain functions implicated in reward, language, and social behavior. Cerebellar Purkinje cells (PCs) make inhibitory GABAergic synapses with their target neurons: other PCs and Lugaro/globular cells via PC axon collaterals, and neurons in the deep cerebellar nuclei (DCN) via PC primary axons. PC-Lugaro/globular cell connections form a cerebellar cortical microcircuit, which is driven by serotonin and noradrenaline. PCs’ primary outputs control not only firing but also synaptic plasticity of DCN neurons following the integration of excitatory and inhibitory inputs in the cerebellar cortex. Thus, strong PC-mediated inhibition is involved in cerebellar functions as a key regulator of cerebellar neural networks. In this review, we focus on physiological characteristics of GABAergic transmission from PCs. First, we introduce monoaminergic modulation of GABAergic transmission at synapses of PC-Lugaro/globular cell as well as PC-large glutamatergic DCN neuron, and a Lugaro/globular cell-incorporated microcircuit. Second, we review the physiological roles of perineuronal nets (PNNs), which are organized components of the extracellular matrix and enwrap the cell bodies and proximal processes, in GABA release from PCs to large glutamatergic DCN neurons and in cerebellar motor learning. Recent evidence suggests that alterations in PNN density in the DCN can regulate cerebellar functions.